Panophthalmitis in a patient with dengue fever. Issue 6 (3rd June 2019) - Kumar, Vimal; Deorari, Vaibhav; Swaroop, Shekhar; Biswas, Ashutosh
Abstract : Dengue fever is known for its life-threatening complications of bleeding and capillary leak syndrome. We report an unusual complication of dengue fever causing panophthalmitis, leading to rapidly progressive painful visual loss within days. Later on, the patient developed secondary bacterial infection of the eyeball and developed multiple brain abscesses due to spread of infection from the eyeball. Culture from pus swab of the right eye grew Staphylococcus epidermidis. The patient was promptly treated with broad spectrum antibiotics and after stabilisation, evisceration of the affected eye was done. Supportive therapy in the form of mechanical ventilation in view of poor sensorium, platelet transfusions for thrombocytopenia and guided fluid therapy was also provided. After multiple challenges in the management of the patient, fortunately, the patient survived but we failed to save his right eye. Therefore, it is necessary to carefully examine all vital organs at an early stage to prevent unfortunate outcome.